China’s new global transport network, railway or waterway? : a comparison of China’s Arctic shipping intention and freight train within One Belt and One Road strategy - Huang, Linyan; Lasserre, Frédéric (China Review Academic Publishers Limited, 2018)
The ice melting in the Arctic Ocean fuels the scenarios of the shorter shipping routes and the access to natural resources. The freight train network link China to Europe market with shorter transport distance. This article confront the challenges over these two emerging transportation. Debated in terms of promising Arctic shipping, our study analyzes from three perspectives the actual slow Arctic shipping progress in China. Unlike scenario of the Arctic shipping, trans-Eurasia freight train within One Belt and One Road framework is developing with accelerated speed. In particular, progressive establishment of the geopolitical collaboration, the railway infrastructure, the increase of trade value proved the success of One Belt and One Road strategy. However, still relying on government intervention, freight train is not yet independent in the market in terms of freight price and market share. Neither of them could replace traditional shipping routes, Arctic shipping seem much less feasible compared with freight train line network. Nevertheless, they still impact global transport mechanism, where straight or canal, such as Malacca, Suez, Panama extremely geopolitically control world’s trade and energy supply pattern. This article contributes to the analysis of ongoing transport affairs within two new short-cut transportations via shipping route and railway and to the geopolitical engagement with China and other neighbor countries. 0